Peran Pendidikan Jasmani Olahraga dan Kesehatan dalam membangun karakter siswa di SD Negeri Tegalrejo 1 - Sri Wahyuningsih; Trisharsiwi Trisharsiwi; Taryatman Taryatman (Universitas Sarjanawiyata Tamansiswa, 2023)
The purpose of this study is to describe the role of physical education, sports, and health in building the character of grade 5A students of SD Negeri Tegalrejo 1. This type of research is descriptive qualitative. Observation, interviews, and documentation are used as data collection techniques. In this study, Miles and Huberman used data analysis techniques consisting of data collection, data reduction, data display, and conclusion. The results of research on the role of physical education, sports, and health in building the character of students at SD Negeri Tegalrejo 1 grade 5A show that 1) physical education, sports, and health support the formation of student character well through learning activities. 2) Teachers' efforts in building character values in Class 5A of SD Negeri Tegalrejo 1 through habituation occur during PJOK learning or sometimes outside of PJOK learning, assisted by school culture, where teachers have their approach in addition to teaching. students who still need orientation. 3) The application of character values of grade 5A students of SD Tegalrejo 1 is evident from the results of observations and interviews, including religious, honest, tolerant, disciplined, social care, environmental care, curiosity, and responsibility. The application of these values can be seen in PJOK learning and outside PJOK lessons.